TINJAUAN KOMUNIKASI ISLAM TENTANG DAMPAK JEJARING SOSIAL FACEBOOK (KASUS PADA MAHASISWA STAIN PAREPARE - Ariyanti Aris; Uswatun hasanah; Iskandar Iskandar (KOMUNIDA : Media Komunikasi dan Dakwah, 2016)
This study aims to determine the review of communications Islam against the facebook social networking users, knowing ethics STAIN students using the facebook social networking in communications Islam, and to investigate the impact of social networking on communications antrapribadi facebook for students STAIN. In the process the existing data, the authors used qualitative data processing. Qualitative research conducted by using data analysis required inductive approach, the method is performed for analyzing the data based on the data or events that are specific to draw general conclusions. Engineering technique used is sampling purposive "sampling technique with a certain considerations". This technique can be defined as a process of sampling by determining in advance the number of samples to be taken, then the sample selection is done based on certain objectives, as long as it does not deviate from the characteristics of the samples were ditetapkan.Populasi of this study are students STAIN Pare Pare, and the sample was 10 students who have been selected by the author. The results of this study showed that a Muslim Facebook users require basic ethics in communicating through facebook. Just as in communication via telephone, which was already in use, communication via facebook also require certain ethical. Even content that is contrary to the teachings of Islam also did not escape were made by students of STAIN Pare Pare. However, the students turned out to take advantage of facebook STAIN Pare Pare as possible, ranging from post status with regard to propaganda, to help provide a comment in the forums Islam. Facebook sophistication did not cause a rift for students STAIN Pare Pare with a friend who is far away, even help students establish a relationship STAIN fixed Parepare though separated by many miles. Post-post uploaded on Facebbok turns giving positive and negative impacts for students STAIN.